Natriuretic Peptide Clearance Receptor (NPR-C) Pathway as a Novel Therapeutic Target in Obesity-Related Heart Failure With Preserved Ejection Fraction (HFpEF) - Egom, Emmanuel Eroume A. (Frontiers in Physiology, 2021)
Heart failure (HF) with preserved ejection fraction (HFpEF) is a major public health problem that is projected to double over the next two decades. Despite the high prevalence of HFpEF, there are currently no FDA approved effective therapies for health-related outcomes in this heterogeneous syndrome making it one the greatest unmet needs in cardiovascular medicine. Additionally, there is a lack of mechanistic understanding about the pathobiology of HFpEF. Phenotyping HFpEF patients into pathobiological homogenous groups may, not only be the first step in understanding the molecular mechanism but may also enable the development of novel targeted therapies. Obesity represents one of the most common comorbidities in HFpEF and may have many cardiovascular effects, making it a viable candidate for phenotyping. Large outcome trials and registries reveal that being obese is one of the strongest independent risk factors for developing HFpEF, and this excess risk may not be explained by traditional cardiovascular risk factors. There is increasing focus on investigating the inter-tissue communication between adipose tissue and the heart, and recent evidence suggests that the Natriuretic Peptide Clearance Receptor (NPR-C) pathway may play a role in the development and pathobiology of obesity-related HFpEF. Therapeutic manipulations of NPR-C pathway may represent new pharmacological strategies in the context of underlying molecular mechanisms.